UTILISING THE MEDIA GAMBLER TO INCREASE THE MOTIVATION OF ENGLISH LANGUAGE LEARNERS IN CLASS VII.A SMPN 1 BUA , LUWU REGENCY - Daming, Srinanengsi; Yanti, Yuliana Agustina; Tanan, Yuliana; Syam, Ummu Haerah; Ufrawati, Ufrawati (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
English is one of the compulsory subjects at school. In studying English with the theme